Risk‐based coalition of cooperative microgrids in electricity market environment. Issue 13 (24th May 2018) - Lahon, Rinalini; Gupta, Chandra Prakash
Abstract : This study proposes an energy management framework for cooperative operation of multiple coupled microgrids, in electricity market environment. The framework focuses on a scalable profit maximisation approach across the entire smart grid for coordinated control and management of the coalition forming microgrids and the utility. The optimal control problem only uses the power exchange schedules as control signals between microgrids. Uncertainties pertaining to renewable power generation and load demand are described via scenarios. In this stochastic framework, conditional value‐at‐risk is considered as a risk measure to lessen the danger to which the aggregator is exposed to because of fluctuating power transactions induced by such uncertainties. The framework is further extended to evaluate the impact of cooperative operation on the portfolio returns of participating microgrids over the project lifetime. Several case studies are simulated in‐order to validate the proposed risk‐constrained framework. The results obtained clearly show that the proposed framework is effective in limiting the risk of the profit variability of the microgrids, at the cost of a small reduction in their expected profit.